1993
DOI: 10.1577/1548-8640(1993)055<0177:ceaolt>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Communications: Eye Abnormalities of Lake Trout Exposed to Gas Supersaturation

Abstract: Lake trout (Salvelinus namaycush) reared for 1 year at six levels of differential (excess) gas pressure (AP 4,17, 33,43, 58, and 75 mm Hg above equilibrium) were examined for incidences of eye abnormalities including nuclear cataracts, hemorrhages, corneal swelling, cloudiness, rupture, and loss of eyes. Frequencies of nuclear cataracts, eye hemorrhages, cloudy corneas, and bilateral anomalies were not directly related to increasing dissolved gas pressures. However, incidences of corneal swelling and of all ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Infestation with eye flukes, Diplostomum spp. and intraocular infections, as well as environmental and toxicological factors may cause irreversible lenticular damage in salmonids (Ashton, Brown & Easty 1969; Sharif, Richards & Sommerville 1980; Fraser, Duncan & Tomlinson 1990; Krise & Smith 1993; Cullen, Monteith‐McMaster & Sivak 1994; Laycock, Schirmer, Bols & Sivak 2000). Genetically linked predisposition in trout and Atlantic salmon have been demonstrated (Kincaid 1989; Wall & Richards 1992; Breck, Bjerkås, Campbell, Arnesen, Haldorsen & Waagbø 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Infestation with eye flukes, Diplostomum spp. and intraocular infections, as well as environmental and toxicological factors may cause irreversible lenticular damage in salmonids (Ashton, Brown & Easty 1969; Sharif, Richards & Sommerville 1980; Fraser, Duncan & Tomlinson 1990; Krise & Smith 1993; Cullen, Monteith‐McMaster & Sivak 1994; Laycock, Schirmer, Bols & Sivak 2000). Genetically linked predisposition in trout and Atlantic salmon have been demonstrated (Kincaid 1989; Wall & Richards 1992; Breck, Bjerkås, Campbell, Arnesen, Haldorsen & Waagbø 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This consistency in operation is important and has not always been achieved. For example, some researchers applied treatments that were dependent on mixing warm and cold water from lakes (Machado et al 1987;Krise and Smith 1993;Mesa and Warren 1997) or pumping water from depth (Beyer et al 1976;Bouck 1980). These types of control systems often varied from month to month, yielding highly variable saturation, water temperature, and gas partial pressure treatments.…”
Section: Discussionmentioning
confidence: 99%
“…To create a gas-supersaturated environment, researchers have used a variety of techniques, including (1) mixing warm and cold water (Machado et al 1987;Krise and Smith 1993;Mesa and Warren 1997), (2) using pressurized water from depth (Beyer et al 1976;Bouck 1980), (3) utilizing air-injected pressure systems (Rucker and Kangas 1974;Gray et al 1982Gray et al , 1985Shrimpton et al 1990;Caldwell and Hinshaw 1994;Schisler et al 1999), or (4) using a combination of heating and air injection (Chamberlain et al 1980). The methods employed generally have created a single saturation level and have not allowed for control of water temperature.…”
mentioning
confidence: 99%
“…Bouck (1984) observed that the TDG pressure in water is different in different seasons. Krise and Smith (1993) and Mesa and Warren (1997) created supersaturated TDG water by mixing hot and cold water artificially. Jiang et al (2008b) carried out field observations in the Minjiang River downstream of the Zipingpu Dam and showed that the water temperature affects TDG supersaturation.…”
Section: Introductionmentioning
confidence: 99%